Observations of the Formation of a Proto-Spot in a Pre-Existing Field Environment - Mariarita Murabito; Ilaria Ermolli; Salvo L. Guglielmino; Paolo Romano; Fabrizio Giorgi (Universe)
Bipolar emerging flux regions (EFRs) form active regions (ARs) that generally evolve into a pre-existing magnetic environment in the solar atmosphere. Reconfiguration of the small- and large-scale magnetic connectivities is invoked to explain a plethora of energy-release phenomena observed at the sites of EFRs. These include brightening events, surges, and jets, whose triggers and relationships are still unclear. In this context, we study the formation of a proto-spot in AR NOAA 11462 by analyzing spectropolarimetric and spectroscopic measurements taken by the Interferometric Bidimensional Spectrometer along the Fe I 630.2 nm and Ca II 854.2 nm lines on 17 April 2012. We complement these high-resolution data with simultaneous SDO satellite observations. The proto-spot forms from magnetic flux and emerges into the photosphere, coalescing following plasma flows in its surroundings. The chromospheric and higher atmosphere observations show that flux emergence occurs in a pre-existing magnetic environment, with small- and large-scale coronal arcades that seemingly shape the proto-spot formation in the upper atmospheric layers. In addition, in the chromosphere, we observe an arch filament system and repeated intense brightening events and surges, likely due to magnetic interactions of the new flux with the pre-existing overlying coronal field. These phenomena have been observed since the early stages of the new flux emergence.